2017
DOI: 10.1016/j.celrep.2017.08.099
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase SCF(Cyclin F) Transmits AKT Signaling to the Cell-Cycle Machinery

Abstract: SUMMARY The oncogenic AKT kinase is a key regulator of apoptosis, cell growth and cell cycle progression. Despite its important role in proliferation, it remains largely unknown how AKT is mechanistically linked to cell cycle. We show here that Cyclin F, a substrate receptor F-box protein for the SCF family of E3 ubiquitin ligases, is a bona fide AKT substrate. Cyclin F expression oscillates throughout the cell cycle, a rare feature among the 69 human F-box proteins, and all of its known substrates are involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…Lambda phosphatase treatment of the mitotically arrested U2OS cell lysates confirmed that both human ORC1 and CDC6 were phosphorylated, since after treatment the proteins moved faster in the gel, similar to Cyclin F protein which is known to be phosphorylated in mitosis (Choudhury et al, 2017;Mavrommati et al, 2018) ( Figure 3E).…”
Section: Cy Motif and Cdk Phosphorylation Sitesmentioning
confidence: 70%
“…Lambda phosphatase treatment of the mitotically arrested U2OS cell lysates confirmed that both human ORC1 and CDC6 were phosphorylated, since after treatment the proteins moved faster in the gel, similar to Cyclin F protein which is known to be phosphorylated in mitosis (Choudhury et al, 2017;Mavrommati et al, 2018) ( Figure 3E).…”
Section: Cy Motif and Cdk Phosphorylation Sitesmentioning
confidence: 70%
“…Previous studies demonstrated that cyclin F functions as a key regulator of the cell cycle (Tetzlaff et al, 2004;Choudhury et al, 2016Choudhury et al, , 2017. Previous studies demonstrated that cyclin F functions as a key regulator of the cell cycle (Tetzlaff et al, 2004;Choudhury et al, 2016Choudhury et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…In an unperturbed cell cycle, cyclin F promotes the degradation of atypical E2Fs to allow a timely G2/M transition. Previous studies demonstrated that cyclin F functions as a key regulator of the cell cycle (Tetzlaff et al, 2004;Choudhury et al, 2016Choudhury et al, , 2017. CCNF, the gene encoding cyclin F, is highly conserved across different species.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Cdh1 collaborates with the retinoblastoma tumor suppressor protein to restrict S‐phase entry (Fay et al , ; Binné et al , ; Buttitta et al , ; The et al , ), and single allelic loss of the Cdh1 gene promotes tumorigenesis in mice (García‐Higuera et al , ). We recently showed that Cdh1 degradation could be driven by upstream signaling through the oncogenic AKT kinase (Choudhury et al , ), which is activated in numerous cancers (Manning & Toker, ). Since, Cezanne is recurrently amplified/overexpressed in cancers, it could promote proliferation and perhaps impact chromosome stability, by antagonizing APC/C.…”
Section: Discussionmentioning
confidence: 99%